Conflict in Islamic Jurisprudence: Noel J. Coulson’s Historical Approach and His Contribution to the Study of Islamic Law - Abdurrahman, Landy Trisna (Institut Agama Islam Negeri (IAIN) Pontianak, 2022)
Islamic jurisprudence (fiqh) has a long history and has stagnated since the Middle Ages, whose impact is still being felt today. Various innovations have been braved enough to violate the boundaries of doctrine between schools of thought in Islamic judicial decisions in its development. It is this issue that Noel J. Coulson describes in Conflict and Tension in Islamic Jurisprudence. This article reviews the approach used by Noel J. Coulson to Islamic jurisprudence by asking two main questions. First, how are Noel J. Coulson’s approach and method in Islamic jurisprudence research? Second, how is Noel J. Coulson’s contribution to the development of Islamic law studies? The writer answered these two questions by using a bibliographic type of research. The author finds that Noel J. Coulson dissects the development of Islamic jurisprudence by using historical and sociological approaches. Noel J. Coulson argues that traditional fiqh (classical to the medieval era), contemporary fiqh and decisions in Islamic law courts constitute an actual legal entity. The author argues that Noel J. Coulson’s historical approach to Islamic law is still relevant so that Islamic law is not considered stagnant.